Gender-based differences in stride and limb dimensions between healthy red-wing tinamou (Rhynchotus rufescens) Temminck, 1815 - de Queiroz, Sandra Aidar [UNESP]; Cooper, Ross Gordon (Tubitak Scientific & Technical Research Council Turkey, 2011)
The red-wing tinamou (Rhynchotus rufescens) is economically important as food. The current study investigated the limb and trunk characteristics in age-matched [year-of-hatch (yoh) 2004 and 2005], gender segregated birds, and determined differences in stride between cocks and hens. The locomotion trial was completed in a corridor of 0.6 x 2.36 m dimension. The girth was significantly higher in cocks than in hens, while body weight was slightly higher in hens. Cocks had a greater height than hens. The time to walk 2.36 m was longer for cocks than for hens. This was related to an attenuated speed and stride length in cocks by comparison with hens. The increased number of strides and reduced stride lengths in cocks suggested their defensive posture by lagging behind the fleeing hens or juveniles. Subtle differences in yoh may have been related to small variances in nutrition, weather, management, age, and reproductive traits. Although the birds born in distinct years were submitted, the net sum of these effects could have potentiated the different performances observed.
Keywords: Limb dimension; Tinamou; stride; Gender